Hypervelocity Gouging Impacts - Cinnamon, John D. (Reston, Va. : American Institute of Aeronautics and Astronautics, 2009)
When materials interact at hypervelocity (on the order of Mach 8.5 and above) unexpected results can occur. This book addresses the effects of hypervelocity impact, summarizing past and present research efforts as well as setting out the theoretical foundation for understanding material interactions at such velocity. It focuses on research conducted at the Holloman Air Force Base High Speed Test Track (HHSTT), which is working toward a test vehicle speed above Mach 10. Researchers have found that as the sled's speed has increased to Mach 8.5, a material interaction has developed that causes "gouging" in the rails and the sled's "shoes", which can lead to catastrophic failure. The author evaluates the HHSTT gouging phenomenon and offers recommendations to mitigate the occurrence of hypervelocity gouging. His insights and recommendations will also find wide applicability in other areas, such as railguns, orbital debris, and weapon design--
Hypervelocity gouging problem overview -- Previous research in the hypervelocity gouging phenomenon -- Theoretical background -- Characterization of gouging -- Constitutive model development -- Validation of constitutive models for midrange strain rates -- Scaled laboratory hypervelocity gouging test -- Validation of constitutive models for high strain rates in hypervelocity impact -- Simulation of HHSTT Hypervelocity gouging scenario -- Conclusions.
"When materials interact at hypervelocity - on the order of Mach 8.5 and above - unexpected results can occur. This book addresses the effects of hypervelocity impact, summarizing past and present research efforts as well as setting out the theoretical foundation for understanding material interactions at such velocity. It focuses on research conducted at the Holloman Air Force Base High Speed Test Track (HHSTT), which is working toward a test vehicle speed above Mach 10. Researchers have found that as the sled's speed has increased to Mach 8.5, a material interaction has developed that causes "gouging" in the rails and the sled's "shoes" - which can lead to catastrophic failure. The author evaluates the HHSTT gouging phenomenon and offers recommendations to mitigate the occurrence of hypervelocity gouging. His insights and recommendations will also find wide applicability in other areas, such as railguns, orbital debris, and weapon design."--Back cover.
Includes bibliographical references and index.
hardcover
Keywords: Impact; Materials -- Dynamic testing; Metals -- Impact testing; Strength of materials